2007
DOI: 10.1016/j.yexcr.2007.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of BTBD1 in mesenchymal differentiation

Abstract: BTBD1 is a recently cloned BTB-domain-containing protein particularly expressed in skeletal muscle and interacting with DNA topoisomerase 1 (Topo1), a key enzyme of cell survival. We have previously demonstrated that stable overexpression of a N-terminal truncated BTBD1 inhibited ex vivo myogenesis but not adipogenesis of pluripotent C2C12 cells. Here, BTBD1 expression was studied in three models of cellular differentiation: myogenesis (C2C12 cells), adipogenesis (3T3-L1 cells) and osteogenesis (hMADS cells). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…BNC1 is involved in cell proliferation, and defective cell proliferation and migration in the PPFs of the developing diaphragm have been proposed to underlie CDH . Given the musculature of the diaphragm, BTBD1 is an interesting candidate involved in myoblast growth and differentiation …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…BNC1 is involved in cell proliferation, and defective cell proliferation and migration in the PPFs of the developing diaphragm have been proposed to underlie CDH . Given the musculature of the diaphragm, BTBD1 is an interesting candidate involved in myoblast growth and differentiation …”
Section: Discussionsupporting
confidence: 86%
“…12 Given the musculature of the diaphragm, BTBD1 is an interesting candidate involved in myoblast growth and differentiation. 65,66 16p11.2 deletions can cause isolated CDH Deletions of 16p11.2 are a risk factor for autism. These deletions were recently reported in 2/45 cases of CDH.…”
Section: Q252 Recurrent Microdeletion Is Associated With Cdhmentioning
confidence: 99%
“…Since the diaphragm is a muscular organ, it is possible that disruption of the BTB (POZ) domain containing 1 ( BTBD1 ) gene, which is essential for myoblast growth and differentiation in vitro, could play a role in development of CDH. [10] However, studies in rodent models suggest that some types of CDH arise from defects in the non-muscular mesenchymal substratum onto which myogenic cells and axons destined to form the neuromuscular component of the diaphragm expand. [11] Further studies have shown that development of posterolateral CDH can be associated with decreased cell proliferation leading to abnormal development of the pleuroperitoneal fold (PPF)—a triangular-shaped embryonic structure which represents the primordial diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrate genomes contain four genes of this BTB-BACK-PHR family: Btbd1-3 and Btbd6. Several studies have found potential substrates for members of this family [15,18,19], but little is known regarding the function or structural basis of the interactions. In our previous work, a yeast two-hybrid screen for proteins that bind Btbd6 identified both Cul3 and a transcriptional repressor protein, Plzf [15].…”
Section: Introductionmentioning
confidence: 99%